Description of a new genus and two new species of Leiodidae (Coleoptera) from Baltic amber using phase contrast synchrotron X-ray microtomography - Perreau, Michel (Zootaxa, 2012)
A new genus and two new amber fossil species of Leiodidae are described: Catops perkovskyi sp. n. (CholevinaeCholevini) and Tafforeus cainosternus gen. n., sp. n. (Leiodinae Pseudoliodini); using virtual dissection by propagationphase contrast synchrotron X-ray microtomography, which allows for visualization of the genital structures in a non-invasive way. The external and internal morphology of the new species is compared to that of the extant related species.Putative evolutionary relationship between Tafforeus and the genus Cainosternum Notman, 1921, and their placement in the tribe Pseudoliodini are discussed.